Disclosure challenges among people living with HIV in Thailand - Lee, Sung-Jae (2013)
One of the main challenges facing people living with HIV (PLH) in Thailand is HIV disclosure. The goal of this study was to examine HIV disclosure barriers and motivators in Northeastern Thailand. Focus groups were conducted with 40 PLH to explore the barriers and motivators. To confirm the themes identified in the focus groups, face-face interviews were conducted with 50 PLH. Focus group findings revealed barriers to HIV disclosure in three domains: perceived stigma, shame and fear of rejection. Motivators to HIV disclosure consisted of the following: coping with illness, seeking help and common experiences. Findings from the face-to-face interviews included the following barriers: fear of privacy breach, fear of rejection and communication difficulties. The motivators to HIV disclosure included seeking supportive relationship, duty to inform and catharsis. Based on these findings, we are currently developing family-focused HIV disclosure intervention in Northeastern Thailand.